Features of development of socialentrepreneurship organizational mechanism of higher education institutions - Saidov Shohruh Mirzo (Genius Journals, 2023)
This article describes in detail the features of the development of socialentrepreneurship organizational mechanism of Higher Educational Institutions, solving the problems created in the field of social-entrepreneurship of Higher Education Institutions, understanding the role and importance of Higher Education Institutions in the development of social-entrepreneurship organizational mechanism.
Keywords: HEI; organizational mechanism; social entrepreneurship